Preparation of perlite based‑zinc nitrate hexahydrate composite for electric radiant floor heating in model building and numerical analysis - Dixit, Prakhar (2022)
Zinc nitrate hexahydrate, an inorganic phase change material, can store high latent heat during its phase change, but it has significant phase transition defects, including form instability, a high degree of supercooling, and phase separation issues. Zinc nitrate hexahydrate/expanded perlite (EP) composite was fabricated by impregnating zinc nitrate hexahydrate into expanded perlite and further 65 wt% PCM-EP composite was coated with paraffin to reduce phase transition imperfections. Scanning electron microscope (SEM) results confirmed that the zinc nitrate hexahydrate could be impregnated into expanded perlite, and paraffin successfully formed a coating layer on the expanded perlite surface. Fourier transform infrared spectroscopy (ATR-IR) confirmed no chemical interactions between zinc nitrate hexahydrate and expanded perlite. The melting and crystallization enthalpies of paraffin-coated PCM composites are 82.24 ± 2.93 kJ kg−1 and 73.32 ± 1.97 kJ kg−1 respectively. The supercooling was reduced from 7 °C to 1 °C owing to numerous nucleation sites on the surface of expanded perlite and coating effect of the paraffin. After the 500 thermal cycles, melting and crystallization enthalpy of coated composite PCM is 78.24 kJ kg−1 and 68.32 kJ kg−1 respectively. Electric radiant floor heating application studies of the coated composite phase change material were performed by varying heat transfer area of building model and amount of composite used. COMSOL Multiphysics 5.6 was used to simulate the thermal buffering performance of the composite in floor heating application. The temperature profile predicted by the simulation was found to be quite close to the experimental data.